Continuous Blood Pressure Estimation Based on Multi-Scale Feature Extraction by the Neural Network With Multi-Task Learning - Jiang, Hengbing; Zou, Lili; Huang, Dequn; Feng, Qianjin (Frontiers in Neuroscience, 2022)
In this paper, a novel method for continuous blood pressure (BP) estimation based on multi-scale feature extraction by the neural network with multi-task learning has been proposed and evaluated. First, we preprocess the target (Electrocardiograph, ECG; Photoplethysmography, PPG) and label signals (arterial blood pressure, ABP), especially using peak-to-peak time limits of signals to eliminate the interference of the false peak. Then, we design a neural network with multi-task learning to extract multi-scale features related to BP, fully excavate and learn the relationship between multi-scale features and BP, and then estimate three BP values simultaneously. Finally, the performance of the developed neural network is verified by using a public multi-parameter intelligent monitoring waveform database. The results show that the mean absolute error ± standard deviation for Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP), and Mean Arterial Pressure (MAP) with the proposed method against reference are 4.04 ± 5.81 mmHg, 2.29 ± 3.55 mmHg, and 2.46 ± 3.58 mmHg, respectively; the correlation coefficients of SBP, DBP, and MAP are 0.96, 0.92, and 0.94 respectively, which meet the Association for the Advancement of Medical Instrumentation (AAMI) standard and reach A level of the British Hypertension Society (BHS) standard. This study provides insights into the improvement of accuracy and efficiency of a continuous blood pressure estimation method with a simple structure and without calibration. The proposed algorithm for BP estimation could potentially enable continuous BP monitoring by mobile health devices.